Membrane androgen receptor characteristics of human ZIP9 (SLC39A) zinc transporter in prostate cancer cells: Androgen-specific activation and involvement of an inhibitory G protein in zinc and MAP kinase signaling. (15th May 2017) - Thomas, Peter; Pang, Yefei; Dong, Jing
Abstract: Characteristics of novel human membrane androgen receptor (mAR), ZIP9 (SLC39A9), were investigated in ZIP9-transfected PC-3 cells (PC3-ZIP9). Ligand blot analysis showed plasma membrane [ 3 H]-T binding corresponds to the position of ZIP9 on Western blots which suggests ZIP9 can bind [ 3 H]-T alone, without a protein partner. Progesterone antagonized testosterone actions, blocking increases in zinc, Erk phosphorylation and apoptosis, further evidence that ZIP9 is specifically activated by androgens. Pre-treatment with GTPγS and pertussis toxin decreased plasma membrane [ 3 H]-T binding and blocked testosterone-induced increases in Erk phosphorylation and intracellular zinc, indicating ZIP9 is coupled to an inhibitory G protein (Gi) that mediates both MAP kinase and zinc signaling. Testosterone treatment of nuclei and mitochondria which express ZIP9 decreased their zinc contents, suggesting ZIP9 also regulates free zinc through releasing it from these intracellular organelles. The results show ZIP9 is a specific Gi coupled-mAR mediating testosterone-induced MAP kinase and zinc signaling in PC3-ZIP9 cells. Graphical abstract: Highlights: [ 3 H]-T binding on a ligand blot corresponds to the position of ZIP9. progesterone antagonizes testosterone signaling and apoptotic actions through ZIP9. ZIP9 is coupled to an inhibitory G protein in transfected PC-3 prostate cancer cells. Gi coupling to ZIP9 is required for testosterone-induced increases in zinc levels. ZIP9 mediates testosterone-induced zinc efflux from nuclei and mitochondria.